The effect of Moringa oleifera L. leaf extract supplementation on the chemical and sensory quality of beef patties cooked to a well-done level - Kartikasari, Lilik Retna; Bayu Setya Hertanto; Farough Heidar Barido; Winny Swastike; Adi Magna Patriadi Nuhriawangsa (Jurnal Ilmu-Ilmu Peternakan, 2023)
This study aimed to evaluate the effect of Moringa oleifera L. leaf extract supplementation on the chemical composition and sensory quality of beef patties cooked to a well-done level. This study used a completely randomized design (CRD) in one direction withfive treatments and five replications. The research treatments included the supplementation of Moringa oleifera L. leaf flour extract (MOE) 0% (P0), 1% (P1), 2% (P2), 3% (P3), and 4% (P4). The variables observed included water content, fat, protein, collagen, and sensory attributes. A 15-cm line scale was used to evaluate the intensity of the attributes tested on beef patties by 30 semi-trained panelists. Chemical and organoleptic quality test data were analyzed using Analysis of Variance. If the treatments had a significant effect, then the analysis was continued using the Tukey Test. The results showed that the addition of Moringa leaf flour extract had a very significant effect (P<0.05) on the chemical quality of beef patties (water, fat, and protein content). The use of Moringa oleifera L. leaf extract at the 2% level produces higher protein and fat levels than the use of 4%. Adding MOE up to 4% can increase the intensity of beef patties' color, aroma, and tenderness (P<0.05). The supplementation of Moringa oleifera L. leaf flour extract at the 2% level can produce beef patties with relatively high protein and fat content and can maintain sensory quality.